Superconductivity in titanium probed by AC magnetic susceptibility to 120 GPa - Song, Jing; Liu, Hongyu; Wang, Xiancheng; Jin, Changqing (Chinese physics B, 2025)
We used a highly sensitive AC magnetic susceptibility technique to probe superconductivity in elemental titanium (Ti) under extreme pressures to 120 GPa in a diamond anvil cell (DAC). The measurements reveal that the critical temperature ( T c ) of Ti rises monotonically with increasing pressure, reaching 6.1 K at 120 GPa. Our results confirm the bulk nature of the superconductivity in Ti, as evidenced by a robust diamagnetic response in the AC magnetic susceptibility. Our work provides a routine technique to probe Meissner effect of elemental superconductors at megabar pressures.